INNOVATION IN SOCIAL SCIENCE LEARNING BASED ON LOCAL WISDOM: HOMBO BATU AS A CULTURAL EDUCATION MEDIA IN SOUTH NIAS - Harefa, Darmawan (Universitas Nias Raya, 2025)
This study aims to explore innovations in Social Science (IPS) learning based on local wisdom by using Hombo Batu as a cultural education media in South Nias. Hombo Batu, a cultural tradition rich in social and educational values, is integrated as a tool in the learning process to introduce students to the importance of local wisdom in a social and cultural context. Through this approach, the study analyzes the potential of Hombo Batu as a learning medium that can strengthen students' understanding of the history, social values, and culture of Nias. The research method used in this study is qualitative, with a case study approach conducted in schools in South Nias. The findings indicate that the use of Hombo Batu in IPS learning not only enhances students' understanding of the learning material but also introduces them to the importance of preserving local wisdom within the context of social development. It is expected that the results of this study will contribute to the development of local culture-based learning methods to improve the quality of education in the region.